Dielectric Loaded Waveguide Filter Design - (:unkn) unknown (IEEE, 2016)
A hollow waveguide is loaded with dielectric slabs to be operated as a band-pass filter in the X-band. Realizing the followed approach practically, the permittivity values of the slabs are chosen. The thickness values of the slabs are optimized to meet the filter requirements. Levenberg-Marquardt optimization algorithm is utilized to solve the given non-linear optimization problem. Drawbacks of the proposed approach are analyzed in terms of optimization parameters and shown with numerical examples.
Keywords: Design Optimization; Inverse Problems; Waveguide Filter Design; SCATTERING